A fullerene-rhodamine B photosensitizer with pH-activated visible-light absorbance/fluorescence/photodynamic therapy. Issue 18 (18th April 2018) - Tang, Qianyun; Xiao, Wanyue; Li, Jiewei; Chen, Dapeng; Zhang, Yewei; Shao, Jinjun; Dong, Xiaochen
Abstract : A heavy-atom-free photosensitizer (C60 -RB) with pH-activable visible-light absorbance enhancement, fluorescence turn-on and triplet excited state generation was designed for tumor bioimaging and photodynamic therapy. Abstract : The development of smart photosensitizers with tumor microenvironment-activable fluorescence turn-on and singlet oxygen generation plays an important role in tumor bioimaging and photodynamic therapy. Herein, a pH-activable heavy-atom-free photosensitizer (C60 -RB) has been successfully synthesized through introducing a fullerene unit onto rhodamine B hydrazide. Under acidic conditions, C60 -RB, having a spirolactam structure, can be activated to its ring-opened structure C60 -RB-H and thus, visible-light absorbance enhancement, fluorescence turn-on and triplet excited state generation can be accomplished. In the presence of hydrion, the fullerene unit in C60 -RB C60 -RB-H acting as an intramolecular spin converter can cause good intersystem crossing, and the energy gap between S1 and T1 (Δ E ST ) is lowered to 0.017 eV. Through encapsulation with amphiphilic DSPE-mPEG2000, water-soluble nanoparticles (NPs) of C60 -RB are obtained. In vitro experiments indicate that C60 -RB NPs are capable of universal cellular uptake and lysosomal activation (pH 4.5–5.0), and they also exhibit excellent photodynamic therapeutic effect. The fluorescence turn-on and efficient singlet oxygen generation enabled by pH-activated C60 -RB NPs testify their great potential applications for cancer diagnosis and treatment.